Integration of Gesture Control with Large Display Environments Using SAGE2 - Thanatorn Boonnak (2019)
© 2018 IEEE. With the ever-increasing amount of information, data scientists continue to explore new technologies that will help them access and interact with data in a variety of domains and situations. One technology of particular interest is Scalable Resolution Shared Displays (SRSD) that use a web-based collaboration middleware called SAGE2. These display systems are ideal for exploring large data sets in data intensive applications; however, interacting with content on these largewalls intuitively and rapidly remains a challenge to be addressed. This work introduces a prototype user interface basedon a simple, hand gesture-based approach to control content in a SAGE2 workspace using the Leap Motion controller. Our implementation and preliminary testing of the interface demonstrates its potential as a more natural interaction modalitywhen exploring big data sets.